Importance of capacity balancing on the electrochemical performance of Li[Ni0.8Co0.1Mn0.1]O2 (NCM811)/silicon full cells - Reuter, Florian; Baasner, Anne; Pampel, Jonas; Piwko, Markus; Doerfler, Susanne; Althues, Holger; Kaskel, Stefan (Journal of The Electrochemical Society, 2019)
In recent years, both silicon thin films and nickel-rich layered oxides have received much attention as promising anode or cathode materials for next generation lithium ion batteries, respectively. In this work, full cells containing Li[Ni0.8Co0.1Mn0.1]O2 (NCM811) as cathode in combination with amorphous columnar silicon thin films as anode are evaluated in coin cells and 3-electrode cells with varying capacity balancing. Full cells with area capacity ratios of negative to positive electrodes (n/p-ratio) reaching from 1.15: 1 to 2.70: 1 are studied. The cells with a high n/p-ratio (2.00: 1 and 2.70: 1) show significantly lower specific capacity of 115 mA h gNCM −1 after 50 cycles of galvanostatic cycling in comparison to 130 mA h gNCM −1 for a cell with a n/p-ratio of 1.15: 1. One reason for this phenomenon is the decline of the initial coulombic efficiency with increasing n/p-ratios. Secondly, through only partial utilization of the silicon anode by using high n/p-ratios, the anode potential is increased at the end of charge. This leads to a higher cathode potential and therefore a faster degradation of the cell. In summary, for designing high performance NCM811/Si full cells, high n/p-ratios should be avoided.
CRIS-Team Scopus Importer:2022-04-14